Individual Differences Facing the COVID-19 Pandemic: The Role of Age, Gender, Personality, and Positive Psychology - Bernabe-Valero, Gloria; Melero-Fuentes, David; De Lima Argimon, Irani I.; Gerbino, Maria (Frontiers in Psychology, 2021)
Research on individual differences in facing the COVID-19 pandemic seems to be crucial in order to design diverse and highly effective intervention strategies. This study uses a sample of 302 North American participants who were recruited through the crowdsourcing platform ProA; different profiles were established, profiling variables of interest in facing the COVID-19 outbreak. Socio-demographic and psychological (personality traits, gratitude, life purpose, and religiosity) variables were explored. These results are of interest if we want to deepen the study of individual differences at both a theoretical and applied level.